2022
DOI: 10.1080/07853890.2022.2045034
|View full text |Cite
|
Sign up to set email alerts
|

Trends in adolescent COVID-19 vaccination receipt and parental intent to vaccinate their adolescent children, United States, July to October, 2021

Abstract: Introduction There was a five-fold increase in COVID-19 hospitalization case counts among children and adolescents between June and October 2021. However, polls suggest that adolescent COVID-19 vaccination coverage has plateaued in the United States. Methods Using the Census Bureau’s Household Pulse Survey, we assessed trends in COVID-19 vaccination among adolescents ages 12–17 years, parents’ intention to vaccinate their adolescent children, and their reasons for not i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 16 publications
2
19
0
Order By: Relevance
“…Despite the accumulating evidence, vaccine hesitancy still remains a global issue . The low uptake of vaccines among children and unwillingness of parents to vaccinate their children have been reported . According to surveys in the US, 25% to 46% of parents were unsure or reluctant to vaccinate their children .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the accumulating evidence, vaccine hesitancy still remains a global issue . The low uptake of vaccines among children and unwillingness of parents to vaccinate their children have been reported . According to surveys in the US, 25% to 46% of parents were unsure or reluctant to vaccinate their children .…”
Section: Discussionmentioning
confidence: 99%
“…21,60,61 The low uptake of vaccines among children and unwillingness of parents to vaccinate their children have been reported. 21,22,62,63 According to surveys in the US, 25% to 46% of parents were unsure or reluctant to vaccinate their children. 22,63,64 While 83% of parents acknowledged that "it would be bad if children got COVID-19," 63 26% did not believe that vaccines would protect their children from COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Concerns are often centered around vaccine side effects, disease severity, and vaccine effectiveness [ 6 , 7 ]. Similar concerns have been expressed about COVID-19 vaccines [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 59%
“…As for the estimated maximum proportion of individuals vaccinated in the 12–17 year old age group, previous literature appears to be aligned with our finding that highly vulnerable counties are on pace to achieve higher vaccination numbers than low and moderate vulnerable counties in Themes 1 and 2. A study conducted on vaccination coverage among adolescents from July to October 2021 reported a large increase in vaccination uptake when parents had an income of <$35,000 ( 31 ). While this study focuses on the U.S. population at large, we nonetheless observe a similar trend in the present study as our snapshot analysis reveals that the disparity between highly vulnerable counties and moderate and low vulnerable counties pertaining to socioeconomic status becomes ameliorated throughout July to October 2021.…”
Section: Discussionmentioning
confidence: 99%